2017
DOI: 10.1161/circep.117.005599
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gadolinium Contrast Enhancement of Radiofrequency Ablation Lesions in Predicting Edema and Chronic Lesion Size

Abstract: Background MRI has been used to acutely visualize radiofrequency (RF) ablation lesions but its accuracy in predicting chronic lesion size is unknown. The main goal of this study was to characterize different areas of enhancement in late gadolinium enhancement (LGE) MRI done immediately after ablation to predict acute edema and chronic lesion size. Methods and Results In a canine model (n=10), ventricular RF lesions were created, using ThermoCool SmartTouch (Biosense Webster) catheter. All animals underwent M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 24 publications
(27 reference statements)
3
76
0
1
Order By: Relevance
“…Our results demonstrate that LGE images acquired about 30 minutes after injection overestimated the chronic lesion size by almost a factor of 4. More recently, it was shown that the MVO region in acute LGE‐MRI acquired at 26.1 minutes after contrast administration is a good predictor of chronic ventricular lesions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate that LGE images acquired about 30 minutes after injection overestimated the chronic lesion size by almost a factor of 4. More recently, it was shown that the MVO region in acute LGE‐MRI acquired at 26.1 minutes after contrast administration is a good predictor of chronic ventricular lesions …”
Section: Discussionmentioning
confidence: 99%
“…To identify such changes in tissue and evaluate lesion formation, late gadolinium enhancement magnetic resonance imaging (LGE‐MRI) has been used acutely and chronically after RF and cryoablation procedures. However, it is difficult to rely on acute LGE‐MRI to accurately predict the size of chronic lesions due to spatially and temporally nonuniform enhancement of ablated areas observed in acute LGE‐MRI …”
Section: Introductionmentioning
confidence: 99%
“…It is appealing to envison imaging approaches that could help determine extent of lesion during the procedure. Real‐time MRI techniques provide an immediate and direct means of measuring ablation‐related tissue changes in addition to improved visualization of the tissue, as shown by numerous prior studies . Despite this appeal of using MRI in real time, the techniques are still being developed and are not ready for clinical use .…”
Section: Discussionmentioning
confidence: 99%
“…CMRI provides enhanced visualization of soft tissues with high spatial and temporal resolution . It can differentiate an acute edema in the setting of ablation from a chronic lesion that ultimately develops.…”
Section: Discussionmentioning
confidence: 99%